Nick Mauss - Transmissions - Kelly, Karen J. 1964-; Schroeder, Barbara (Dancing Foxes Press, 2020)
Nick Mauss's Transmissions / Scott Rothkopf -- Gesturing personae, with performance photography by Ken Okiishi and Paula Court / Nick Mauss -- Relâche/Relax / Joshua Lubin-Levy -- Legacies of exchange / Allie Tepper -- Nick Mauss in conversation with Dancers Alexandra Albrecht, Kristina Bermudez, Maggie Cloud, Brandon Collwes, Ahmaud Culver, Jasmine Hearn, Elizabeth Hepp, Forrest Hersey, Alexandra Jacob, Burr Johnson, Maki Kitahara, Evelyn Kocak, Benedict Nguyen, Matilda Sakamoto, Quenton Stuckey, and Anna Thérèsa Witenberg
Includes bibliographical references
Impressum: "The publication of this volume follows the exhibition Nick Mauss: Transmissions, which was on view at the Whitney Museum of American Art, New York, March 16-May 14, 2018, and organized by Scott Rothkopf ... and Elisabeth Sussman ... "
2002
Keywords: Mauss, Nick -- 1980-; Tanz -- Motiv; Art and dance / New York (State) / New York / History / 20th century / Exhibitions; Avant-garde (Aesthetics) / New York (State) / New York / History / 20th century / Exhibitions; Bildband; Ausstellungskatalog -- Whitney Museum of American Art -- 16.03.2018-14.05.2018 -- New York, NY